Selective SERS Sensing Modulated by Functionalized Mesoporous Films - López Puente, Vanesa; Angelome, Paula Cecilia; Soler Illia, Galo Juan de Avila Arturo; Liz-Marzán, Luis M. (American Chemical Society, 2015)
Fil: López Puente, Vanesa. Universidad de Vigo; España